PENGGUNAAN KONJUNGSI DALAM TINDAK TUTUR MENGKRITIK PADA ULASAN TRANSPORTASI UMUM DI MEDIA YOUTUBE - Agus Hartanto, Rudi; Andesta Putri, Silfia; Sumarlam, Sumarlam (Translation and Linguistics (Transling), 2022)
This research is a syntaxis study focused on the use of conjunction in a speech act. The purpose of this study is to describe the frequency of conjunction and its accuracy in speech act of critique at a YouTube channel. The type of this research is descriptive qualitative. The data were collected by watched method and written technique. The data for this study are the conjunction used in speech act of critique. The analysis tool in this study is distribution method. The result of this study shows there are some kinds of conjunctions and its frequency of occurrence in speech act of critique. Then the result of this study indicates there are some functions of conjunction that affected the accuracy of its use.